2003
DOI: 10.1523/jneurosci.23-27-09016.2003
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Fear Memory by Histamine-Elicited ERK2 Activation in Hippocampal CA3 Cells

Abstract: Consolidation of associative memories appears to require extracellular signal-related kinase2 (ERK2) activation, which is modulated by several factors, including neurotransmitter receptor stimulation. Here we show that in vitro stimulation of either H2 or H3 histaminergic receptors activates ERK2 in hippocampal CA3 pyramidal cells. In behaving animals, bilateral posttraining injections into the dorsal hippocampus of histamine H2 or H3 receptor agonists improve memory consolidation after contextual fear conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 36 publications
7
83
3
Order By: Relevance
“…Thioperamide microinjected in the BLA impairs consolidation of fear memory in rats [32]. Procognitive effects are observed in the fear conditioning paradigm when H 3 R of the BLA or the hippocampus are activated rather than blocked [32][33][34], an observation opposite to the results obtained after systemic injections of thioperamide or Pitolisant (Charlier and Tirelli [14]; present results). Many studies have shown that the NBM plays a central role in memory consolidation of information acquired in the fear conditioning task [6,35].…”
Section: Discussioncontrasting
confidence: 92%
“…Thioperamide microinjected in the BLA impairs consolidation of fear memory in rats [32]. Procognitive effects are observed in the fear conditioning paradigm when H 3 R of the BLA or the hippocampus are activated rather than blocked [32][33][34], an observation opposite to the results obtained after systemic injections of thioperamide or Pitolisant (Charlier and Tirelli [14]; present results). Many studies have shown that the NBM plays a central role in memory consolidation of information acquired in the fear conditioning task [6,35].…”
Section: Discussioncontrasting
confidence: 92%
“…Proxyfan behaves as a protean agonist, as it shows a spectrum of activities that range from full agonist to full inverse agonist at distinct functional responses within different animal species. In the learning paradigm used in the present study, contextual fear conditioning, proxyfan mimicked the memory-enhancing effect of H 3 receptor agonists administered locally either in the amygdala (Cangioli et al, 2002), or in the hippocampus (Giovannini et al, 2003) in contextual fear conditioning. Accordingly, rats that received systemic administrations of proxyfan showed a stronger response to the footshock-context association, as they spent more time freezing in the retention test.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, post-training administrations of the H 3 receptor antagonists/inverse agonists thioperamide or clobenpropit into the basolateral amygdala impair memory for aversive events (Passani et al, 2001), whereas agonists such as R-a-methylhistamine improve the expression of fear memory after contextual fear conditioning (Cangioli et al, 2002). In the same learning paradigm, post-training injections into the dorsal hippocampus of R-a-methylhistamine improve memory consolidation (Giovannini et al, 2003). Almost invariably, the behavioural effects of histaminergic compounds have been studied following systemic or local administration into small brain regions, which are known to be crucial for the behavioural response under study.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that unoperated and postconditioning ketamine-anesthetized rats that received intracerebral saline injections exhibited similar freezing responses to TC (Sacchetti et al 1999;Giovannini et al 2003), thus suggesting that these manipulations do not interfere with consolidation. Ketamine-anesthetized animals display frequency-specific receptive field plasticity induced by Pavlovian fear conditioning (Lennartz and Weinberger 1992).…”
mentioning
confidence: 91%